ANALISIS BANDWAGON EFFECT PADA PERILAKU SISWA DALAM KONTEKS INTERAKSI SOSIAL DI LINGKUNGAN MIN 29 ACEH BESAR - Helmi Suardi; Widya Riskina (Jurnal Genta Mulia, 2026)
The bandwagon effect phenomenon often manifests among elementary school students. This conduct arises when pupils conform to the acts of the majority in a group without critical evaluation, largely to attain social approval.Within the educational environment, the bandwagon effect can result in detrimental outcomes, such as bullying, social ostracism, and a reduction in independent thought. This research utilized a qualitative approach through a descriptive phenomenological methodology. Data were gathered via interviews with students, form teacher  and teaching methodology teacher.The data were examined through an interpretive model inside a qualitative research framework, with processing and conclusions derived from field results.The results demonstrate that multiple elements facilitate the establishment of the bandwagon effect, including peer influence, peer pressure, economic situations, social standing, prevailing cultural trends, and the influence of authoritative personalities in the classroom. Moreover, educators are crucial in alleviating the adverse effects of student behavior by offering ethical direction, promoting constructive conduct, nurturing independent thought, cultivating empathy and tolerance, and partnering with parents.In conclusion, the bandwagon effect is a complex phenomenon influenced by psychological, social, economic, and cultural factors. Educators have a pivotal role in directing pupils towards constructive behavior through character education, ethical training, and the collaborative support of both educational and familial contexts.